Improving local well-being through tourism: A study of the economic impact of tourism in Malang City, Indonesia - Puspitasari, Reny; Matfuqin, Iqbal Mahmud (Journal of Rural Tourism, 2024)
Purpose - This study examines the economic impact of tourism on local income in Malang City, analyzing its contribution to the region's economy through a literature review.Methodology/Design/Approach - Using a literature review, the study analyzes existing data on tourism’s effects on local income, job creation, infrastructure, and quality of life.Findings - Tourism boosts regional income, creates jobs, improves infrastructure, and enhances living standards. It diversifies the local economy by supporting industries like creative services. However, challenges like over-dependence, income inequality, and socio-cultural issues need addressing, with sustainable tourism management essential for long-term benefits.Originality/Value - The study emphasizes the importance of sustainable tourism management for long-term growth, highlighting the need for regulations, infrastructure, and human resource development, while offering policy recommendations to maximize benefits and minimize negative impacts.